OBJECTIVES AND METHODS OF ECONOMICAL GEOLOGY - BODIUK, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Directions of researches of geological slovley are grounded, including resources of bowels of the earth, economy of resources, organizational and legal providing. Application of groups of methods of geological, economical, financial, theoretical, statistical, calculation and balance estimations is analysed.